Haruan (Channastriatus) extract as halal innovation productsfor healing of gastric ulcer: preliminary investigation - Azemi, Ahmad Khusairi; Md Tohid, Siti Farah; Somchit, Muhammad Nazrul; Mat Jais, Abdul Manan; Zakaria, Zainul Amiruddin (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
Channastriatus (Haruan), a freshwater and snakehead fish, is traditionally used by the Malay to heal wound and lessens post-operative pain and discomfort. The objective of the present study is to elucidate the gastroprotective activity of chloroform:metanol extract of C. striatus fillet. The fillets were extracted using the methanol: chloroform (2:1; v/v) solvent system. The extract (labeled as MCECS), prepared in the doses of 50, 250, and 500 mg/kg, was orally administered into rats for 7 continuous days and then the animals were subjected to the ethanol- and indomethacin-induced gastric ulcer models. Following the euthanization of treated rats, the stomach was callected for macroscopic and microscopic analysis. The results showed that oral administration of MCECS exhibited significant (p<0.05) and dose-dependent antiulcer activity when assessed using both models of gastric ulcer. In addition, the macroscopic findings were supported by the microscopic observations. In conclusion, C. striatus extract exerted remarkable antiulcer activity that warranted in-depth studies in an attempt to develop its extract as a halal-based product.